2011
DOI: 10.1007/s10750-011-0890-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of food-web structure on the quantity and the elemental quality of sedimenting material in shallow lakes

Abstract: Sedimentation is a key process in lake functioning, and plays an important role in nutrient and carbon cycles at both regional and global scales. Several biological processes have been shown as quantitatively affecting sedimentation, but very few works have tried to relate the structure of aquatic communities and the quality of sinking organic matter. We tested in a mesocosm study how food-web structure affects quantitatively and qualitatively sedimentation in eutrophic systems. We carried out a long-term expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 62 publications
6
27
0
Order By: Relevance
“…These results indicate that the C ⁄ N ratio was not a valuable proxy for RDS biodegradability in our experiment and support the previous suggestions that sediment C ⁄ N ratio alone does not allow assessment of sediment biodegradability and quality (e.g. proteins, sugars and PUFAs) than RDS from the fishless treatment (Allard et al, 2011;Danger et al, 2012). Our results are opposite to the findings of Sander & Kalff (1993), who found a positive linear correlation between the bacterial production in freshwater sediments and their organic matter content.…”
Section: Relationship Between the Elemental And Biochemical Compositisupporting
confidence: 60%
See 4 more Smart Citations
“…These results indicate that the C ⁄ N ratio was not a valuable proxy for RDS biodegradability in our experiment and support the previous suggestions that sediment C ⁄ N ratio alone does not allow assessment of sediment biodegradability and quality (e.g. proteins, sugars and PUFAs) than RDS from the fishless treatment (Allard et al, 2011;Danger et al, 2012). Our results are opposite to the findings of Sander & Kalff (1993), who found a positive linear correlation between the bacterial production in freshwater sediments and their organic matter content.…”
Section: Relationship Between the Elemental And Biochemical Compositisupporting
confidence: 60%
“…In a recent long-term experiment in mesocosms, Danger et al (2012) confirmed this quantitative effect. Moreover, Danger et al (2012), at the end of the experiment, found higher contents of proteins and sugars in RDS from fish enclosures than in RDS from fishless ones. These authors first confirmed that sedimentation rates were higher in fish enclosures than in fishless ones.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations